SAT0630 Extra-articular musculoskeletal involvement in juvenile idiopathic arthritis: clinical and ultrasonografic findings. (15th June 2017) - Ravagnani, V; Licciardi, F; Montin, D; Santarelli, F; Martino, S; Cirone, C
Abstract : Background: in Juvenile Idiopathic arthritis (JIA), musculoskeletal ultrasound (MSUS) has been proven to be more sensitive than clinical evaluation in detecting articular synovitis. Nevertheless, many studies report a variable percentage of clinically active joints, that are judged normal by ultrasound examination. In absence of a feasible and reliable gold standard for pediatric synovitis (histology or MRI), this point may weaken the confidence in ultrasound, that is nevertheless perceived as an interesting tool, in the management of JIA. Objectives: This preliminary study investigates the possibility that sometimes the clinically detected synovitis could be missed by ultrasound, because of its extra-articular localization. Methods: 43 consecutive children affected by JIA underwent separated clinical and ultrasound assessments, blindly, in the same day. Patients were followed up in a pediatric Rheumatology Unit. The following clinical data were collected: age, sex, disease duration, subset of JIA, ongoing therapy, previous therapy, disease activity. By MSUS, the synovitis was investigated bilaterally, both in gray scale and power Doppler, in the MCP and subtalar joints, wrists, knees, ankles, in the flexor and extensor tendons of the wrist and hand, in the anterior, medial and lateral tendons of the ankle, in the synovial bursae of knee and ankle. The possible involvement of the entheses was also investigated. The definition of ultrasonographic synovitis was based on the preliminary OMERACT definitions of synovitis in children. The inter and intra observer reproducibility of the MSUS examination was tested, independently, both between two operators and through a second assessment of the stored images. Results: 43 children affected by JIA were recruited, in the outpatient clinic of the Regina Margherita Pediatric Hospital of Torino, Italy. They were 9 boys and 34 girls, median age 7, 7 (IQR 5, 5–10, 1), 27 oligoarticular, 11 poliarticular, 4 psoriatic arthritis, 1 undifferentiated arthritis. The median disease duration was 44 months (IQR: 20, 5–61, 5), 20 patients in remission, 23 with active disease. 774 joints, 1548 synovial sheaths, 430 entheses and 258 synovial bursae were assessed. The physical examination detected inflammation in 54 joints, 33 tendons, 0 entheses, 0 bursae. Ultrasound abnormalities were found in 62 joints, 73 tendons, 8 bursae, 0 entheses. Overall physical examination and MSUS showed good concordance even if MSUS was more sensitive especially in detecting extra-articular locations. Conclusions: If the extra-articular locations of synovitis are taken in consideration during the ultrasound examination, there is a good sensitivity of MSUS and a better concordance between clinical and MSUS assessment of JIA. MSUS seems more accurate than physical assessment in detecting the exact position of the inflamed synovial membrane in each anatomical location (joint, synovial sheath, synovial bursa). It could be helpful not only for better addressing the injective procedures, but also for a global quantification of the synovitis (both intra and extra-articular), even if the exact clinical meaning of these ultrasound findings is still unknown, in terms of response to treatments and prognosis. References: Magni-Manzoni S. Arthritis and rheumatism. 2009 Nov 15; 61(11):1497–1504. Roth J. Arthritis Care Res (Hoboken). 2016 Oct 16. Disclosure of Interest: None declared